Identifikasi Tumbuhan Famili Myrtaceae di Kawasan Jalan Sukarela Timur, Desa Lau Dendang, Kecamatan Percut Sei Tuan - Sinaga, Fuja Adinda; Faisal, Muhammad; Sabila, Moza Hanu; Rahma, Nur Izzaty; Safitri, Yenni (LPPPI Publishing, 2025)
Indonesia, as a tropical country with high biodiversity, is home to over 20,000 flowering plant species, with around 40% of these species being endemic. One of the significant plant families contributing to Indonesia's biodiversity is Myrtaceae (the guava family), which includes more than 5,500 species. This study aims to identify and inventory the Myrtaceae species in the Sukarela Timur Street area, Lau Dendang Village, Percut Sei Tuan District, Deli Serdang, as well as analyze their morphology and distribution. The research was conducted using exploration and observation methods, and the results identified four Myrtaceae species: Syzygium aqueum, Syzygium formosanum, Syzygium malaccense, and Psidium guajava. These four species have significant economic potential and ecological benefits, serving as food, medicine, and ornamental plants. This study contributes to the understanding of plant diversity in the area and the potential use of Myrtaceae plants in daily life.